"The More We Can Try to Open Them Up, the Better It Will Be for Their Integration": Integration and the Coercive Assimilation of Muslim Youth. Issue 2 (3rd April 2017) - Jaffe-Walter, Reva
ABSTRACT: Capitalizing on national anxieties, right wing populist leaders promise to enforce national borders with new constellations of policies that regulate and exclude Muslim bodies. Using the theoretical tool of "technologies of concern" (Jaffe-Walter, 2016), this essay critiques how state security discourses operate through public schools. Drawing on ethnographic research with Muslim youth in a Danish public school and an analysis of European integration policies, the author analyzes how policies and practices that ostensibly support young people's integration enact everyday violence and coercive assimilation. Highlighting the perspectives of the young people she worked with, the author argues that state efforts to transform Muslim students into acceptable subjects of the nation-state encouraged their alienation and marginalization.